2017
DOI: 10.1155/2017/8236325
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins A-I, B, and C-III and Obesity in Young Adult Cherokee

Abstract: Since young adult Cherokee are at increased risk for both diabetes and cardiovascular disease, we assessed association of apolipoproteins (A-I, B, and C-III in non-HDL and HDL) with obesity and related risk factors. Obese participants (BMI ≥ 30) aged 20–40 years (n = 476) were studied. Metabolically healthy obese (MHO) individuals were defined as not having any of four components of the ATP-III metabolic syndrome after exclusion of waist circumference, and obese participants not being MHO were defined as metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
4
0
3
Order By: Relevance
“…Insulin resistance, measured with the homeostasis index (HOMA-IR), correlated with apoB in this study supports the association of insulin resistance with lipoprotein transport. The results of the present study are in agreement with the previous study on 476 subjects, demonstrating that apoB correlated with insulin resistance (HOMA-IR) [12].…”
Section: Ldl-c and Tg)supporting
confidence: 93%
“…Insulin resistance, measured with the homeostasis index (HOMA-IR), correlated with apoB in this study supports the association of insulin resistance with lipoprotein transport. The results of the present study are in agreement with the previous study on 476 subjects, demonstrating that apoB correlated with insulin resistance (HOMA-IR) [12].…”
Section: Ldl-c and Tg)supporting
confidence: 93%
“…Recently, apolipoproteins were associated to a higher risk for DM2. A strong association of apolipoprotein with BMI has already been demonstrated with a decrease in its concentration in overweight individuals (Wang, Blackett, Khan & Lee 2017). Some studies have observed a significantly BMI-related increase but with decrease in overweight individuals in the APOH protein levels in DM2 individuals compared to healthy individuals (Gómez- Cardona et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…A possible hypothesis is that the improvement in psychopathology that accompanies changes in ApoA1 and ApoB levels may be a side effect indicating the efficacy of antipsychotic drugs, similar to the effect of antipsychotic-induced weight gain [ 51 , 71 ]. A number of literatures have revealed that obesity increases the ApoB /ApoA1 ratio [ 72 ] and that ApoA1 levels were positively associated with the risk of metabolically healthy obesity (MHO), but the ApoB /ApoA1 ratio is negatively associated [ 73 ].…”
Section: Discussionmentioning
confidence: 99%